Hajj Fund Management in Academic Journey - Uula, Mimma Maripatul (Journal of Islamic Economics Literatures, 2025)
This study aims to see the development of research on the topic of "Hajj Fund Management" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Hajj Fund Management" which comes from the Dimension database with a total of 81 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Hajj Fund Management" research development in the world. The results of the study found that in bibliometric author mapping the authors who published the most research on the theme of "Hajj Fund Management" were Marliyah, Marliyah; Andespa, Roni; Wirdyaningsih; Jayaprawira, Acep R; Oktavia, Novi Tri; Nasution, Nursanita; Zakiruddin, Muhammad Aziz; and Witjaksono, Beny. Furthermore, based on bibliometric keyword mapping, there are 3 clusters with the most used words including pilgrim, religion, ministry, law, development, product, Islamic bank, contract, value, regulation, and risk. Then, the topic of research lines related to Hajj Fund Management is Wakalah Contract in Hajj Financial Management, Impact of Covid on Hajj Fund Management and Hajj Fund Risk Management Issues.